The Study of Specific Surface Area from Carbonat Rock Using Micro Computed Tomography (µ-CT) - Habibi, Mahendra Risky; Niyartama, Thaqibul Fikri (Proceeding International Conference on Science and Engineering, 2017)
Carbonate rocks have been scanned and reconstructed in order to get the value of specific surface area. We get it from the reservoir at a depth of 1000 metres in South Sumatra. Skyscan Micro-CT 1173 is used for throwing and thresholding images using Global Otshu to characterize rocks. Our calculation result shows that the value of specific surface area of carbonate rocks show results 100 to 10-2 using the programming Algorithm Fuzzy C-Mean. The difference in values far enough that it can be assumed that the carbonate rocks have a heterogeneous surface area. In addition, histogram model shows the similarity of the sample. The macro sample has the same characteristics as the micro sample.